Device Programming for His Bundle Pacing - Burri, Haran (Circ Arrhythm Electrophysiol, 2019)
Although permanent His bundle pacing (HBP) was first reported almost two decades ago, it is only recently gaining wider adoption, following facilitation of the implant procedure by dedicated tools. An additional challenge is programming the system, as HBP may have specific configurations and require special considerations which current implantable pulse generators are not designed for. The aim of this article is to provide practical recommendations for programming HBP in order to deliver optimal therapy and ensure patient safety.